Quantification of metallic artifact on CT associated with titanium pedicle screws - Lewis, M. J.; Early, P. J.; Bergman, R.; Love, K.; Nelson, N. (Frontiers in Veterinary Science, 2024)
Background In dogs undergoing vertebral column stabilization, post-operative computed tomography (CT) evaluates implant placement. The impact on the interpretation of metallic artifact associated with titanium implants in dogs remains to be established. Our objective was to quantify metallic artifact on CT associated with titanium pedicle screws. Methods The study design included an in vitro model and a retrospective review of 11 dogs with vertebral column stabilization. Twenty four titanium pedicle screws (6 each: 2.0 mm, 2.7 mm, 3.5 mm, and 4.5 mm) were inserted into a 20% ballistic gel, and CT scan of the construct was performed. Three blinded raters used a bone window to measure the maximum width (effective size) of each screw, one rater measured effective size using an ultrawide window and 45 titanium pedicle screws (3×2.0 mm, 5×2.7 mm, 30×3.5 mm, and 7×4.5 mm) in 11 clinical cases. Effective size measurements were compared to actual screw sizes. Results The effective size was 26.9–43.8%, 9.2–18.5%, and 21.1–30.5% larger than the actual size for the in vitro system (bone window), in vitro system (ultrawide window), and clinical cases, respectively. The mean gross difference for the in vitro measurements varied by implant size (p < 0.001) and was positively correlated with implant size (r = 0.846), but the mean percentage difference was negatively correlated with implant size (p < 0.001). Overestimation was larger for the in vitro model bone window compared to the ultrawide window (p < 0.001) and clinical cases (p = 0.001). Conclusion Metallic artifact associated with titanium pedicle screws on CT resulted in an overestimation of screw size. This information might aid in the interpretation of implant placement on post-operative imaging.